Isolation and Identification of Staphylococcus spp. in Fresh Beef - Goja, A.M.; Ahmed, T.A.A.; Saeed, S.A.M.; Dirar, H.A. (Pakistan Journal of Nutrition, 2013)
Forty samples of fresh meat (beef) were randomly sampled from Khartoum, Omdurman and Bahri in Khartoum State, Sudan and analyzed microbiologically for the bacterial load and Staphylococcus (Staph.) count and identify Staph. spp. present in fresh meat. Total viable count ranged from 4.78 x 104 to 3.39 x 105 cfu/g and Staph. count ranged from 3.23 x 103 to 8.7 x 103. A total of 58 Staph. isolates belonging to 19 species of Staphylococcus genus were grouped as follows:1) coagulase-positive species, was Staphylococcus aureus, 2) coagulase-negative species (Novobiocin-sensitive): ten isolates, Staph. epidermidis, Staph. caseolyticus, Staph. lugdunensis, Staph. chromogenes, Staph. capitis, Staph. felis, Staph. warneri, Staph. haemolyticus, Staph. capitis ssp. urealyticus and Staph. hycius., 3) coagulase-negative species (Novobiocin-resistant): eight isolates, Staph. saprophyticus, Staph. xylosus, Staph. Kloosii, Staph. lentus, Staph. cohni, Staph. sciuri, Staph. gallinarum and Staph. cohni ssp. urealyticus. The frequency of isolation of staphylococci in Khartoum State was higher in Omdurman City 23(39.7 %) followed by Bahri City 18 (31%) and Khartoum City 17(29.3%). Among these isolates of staphylococci, Staph. epidermidis, Staph. aureus, Staph. caseolyticus and Staph. saprophyticus were the most abundant isolates. Statistical analysis of the microbial load and total staphylococci count showed no significant difference between the Cities (P>0.05).